Pengukuran Kinerja Keuangan Bank Syariah Indonesia Pasca Merger Menggunakan Pendekatan Islamicity Performance Index - M. Zaky Mubarak Lubis; Gusti Dirga Alfakhri Putra; Hidayatul Husna (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to measure the performance of Indonesian Sharia Banks. Bank Syariah Indonesia is a bank resulting from the merger of three state-owned sharia commercial banks, namely Bank Rakyat Indonesia Syariah, Bank Negara Indonesia Syariah and Bank Syariah Mandiri. Previously, research on these 3 banks had been carried out before the merger occurred. This study seeks to see the performance of Indonesian Islamic Banks after the merger using the Islamicity Performance Index approach. The data used is Bank Syariah Indonesia annual report data for 2021. The results of this study show that two indicators have very satisfactory values, namely Islamic Investment vs. Non-Islamic Investment and Islamic Income vs. Non-Islamic Income, the Equitable Distribution Ratio indicator has a fairly good value, the Profit Sharing Ratio indicator has an unsatisfactory value, and the last two indicators, namely the Zakat Performance Ratio and the Director-Employee Welfare Ratio have very unsatisfactory values.